A Review of the Utilization of Recycled Powder from Concrete Waste as a Cement Partial Replacement in Cement-Based Materials: Fundamental Properties and Activation Methods - Kubilay Kaptan; Sandra Cunha; José Aguiar (Applied Sciences)
Recycled powder (RP) is the primary by-product generated during the reclamation process of construction and demolition waste (CDW). There is existing literature on the use of RP as supplemental cementitious materials (SCMs) in cement-based materials, but a comprehensive evaluation on the characteristics of RP generated from concrete waste has been missing until now. This paper critically reviews the use of RP from concrete waste in cement-based materials, as concrete waste makes up a significant amount of CDW and other components have designated recycling methods. In this sense, this study conducted a critical analysis on the use of RP as an SCM, using detailed literature research. The technology used for producing RP is detailed along with its chemical, mineralogy, and microstructural characteristics. Fresh-state properties in cementitious matrices with RP are introduced with the view of mechanical grinding, thermal activation, carbonation, chemical treatment, biomineralization, mineral addition, nano activation, and carbonation. The review highlights the significant potential of utilizing RP in cement-based materials. Specifically, RP can be advantageously utilized in the production of value-added construction materials.